Penambahan Sari Kurma sebagai Substrat Antibakteri pada Minuman Whey Fermentasi - J. K. Negara; M. Arifin; E. Taufik; T. Suryati (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2021)
Whey from cheese is still underutilized in Indonesia which has the potential to cause environmentalpollution. One alternative to whey processing is to make a fermented whey drink with the additionof date palm juice as a mixture. Dates juice is expected to provide additional nutrition for lactic acidbacteria (LAB) in the fermentation process. The purpose of this study was to determine the antibacterialproperties of whey fermented beverage products with the addition of date juice. The study was conductedusing a randomized block design (RBD) with six groups of sampling treatment with P0; 0% as a control(whey: date juice 100: 0 v / v), P2; 10% (90: 10 v / v), P2; 15% (85: 15 v / v) and P3; 20% (80: 20 v / v).The results of this study indicate that the fermented whey drink with the addition of date juice fermentedwith the bacteria Lactobacillus fermentum B111K (L. fermentum) for 24 hours has been shown to have ahigher antibacterial ability at the level of 20% compared to controls who were not given additional datejuice.